Twórczość Romana Jaworskiego początkiem nurtu parodystyczno-groteskowego w literaturze polskiej - Zwierzchowska, Katarzyna (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2011)
Many researchers on the 20th century literature and art locate Roman Jaworski‘s artistic work on the border of grotesque achievements. The author of Historia maniaków, as the only writer of the Young Poland, with full awareness created and materialised his own theory of this category. In the work of writers preceding his artistic work one can see features of the grotesque, which was expressed in every epoch. However, it was not enriched before the 20th century. Even today it is difficult to define it clearly.The author of Historia maniaków remained for many years in the shadow of the future lucky ones of grotesque. Undoubtedly Jaworski did not influence the grotesque in such a radical way as Witkacy, Gombrowicz or Mrożek. However, because of the pioneering nature of his interest in the grotesque and the full awareness in referring to its attributes, one should acknowledge the author of Hamlet wtórny as the greatest authors of this genre. Roman Jaworski‘s novel Wesele hrabiego Orgaza initiated the trend of catastrophic literature which in later years had many followers.